Unusual presentation of melioidosis in a returning traveler - Barry, Mazin (IDCases, 2020)
Melioidosis is endemic in Southeast Asia and Australia and cases outside those regions are often travel related. We present a case of melioidosis in a man, with no known risk factors who had an unusual presentation with an infected abdominal aortic aneurysm by Burkholderia pseudomallei in Saudi Arabia, a country with no previous reported cases of this infection. It occurred after traveling to Thailand and he was treated successfully with medical therapy and surgical intervention.